2004
DOI: 10.1192/bjp.184.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy for command hallucinations: randomised controlled trial

Abstract: The results support the efficacy of cognitive therapy for CTCH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 22 publications
4
201
0
2
Order By: Relevance
“…If so, future studies may best examine more targeted methods and effects rather than examine effects on positive symptoms in combination. 34,[36][37][38] It should also be noted that ACT protocols vary with problem presentation 39 and ACT for psychosis is still in its infancy thus further protocol refinement is likely required. For example, entrenched avoidant adaptation is a key challenge in chronic presentations: our preliminary recommendation is that dose be consistent with the 15 plus sessions established for CBTp and that the procedures on cost of current coping and engendering hope for change be extended.…”
Section: Effect On Positive Symptomsmentioning
confidence: 99%
“…If so, future studies may best examine more targeted methods and effects rather than examine effects on positive symptoms in combination. 34,[36][37][38] It should also be noted that ACT protocols vary with problem presentation 39 and ACT for psychosis is still in its infancy thus further protocol refinement is likely required. For example, entrenched avoidant adaptation is a key challenge in chronic presentations: our preliminary recommendation is that dose be consistent with the 15 plus sessions established for CBTp and that the procedures on cost of current coping and engendering hope for change be extended.…”
Section: Effect On Positive Symptomsmentioning
confidence: 99%
“…In sum, as shown by the work of Birchwood et al, the distress arising from the activity of voices can be understood by reference to the individual's relationship with the voice, rather than voice content, topography or illness characteristics alone (Birchwood & Chadwick, 1997;Birchwood, Meaden, Trower, & Plaistow, 2000 (Beck & Rector, 2004;Gaudiano, 2005;Temple, 2004), which has shown itself to be effective in reducing the transition to psychosis in people at ultra-high risk, becoming proposed as an acceptable alternative to antipsychotic medication (Morrison, French et al, 2004, 2007. Likewise, cognitive-behavioural therapy has emerged as effective in changing beliefs about the power and omnipotence of the voices and in reducing the distress and depression associated with them, and hence in reducing compliance (Farhall et al, 2007;Trower et al, 2004).…”
Section: Resituating Hallucinations In the Context Of The Person And mentioning
confidence: 99%
“…Where specific symptoms, such as command hallucinations (10), have been targeted, meta-analyses have also given positive results. A recent study focusing specifically on negative symptoms (11) likewise demonstrated a statistically significant and clinically meaningful benefit for adjunctive CBT.…”
Section: Schizophrenia and Related Psychotic Disordersmentioning
confidence: 99%